KETERAMPILAN BERTANYA DAN MEMBERI PENGUATAN GURU DALAM PEMBELAJARAN DARING DI TINGKAT SD PADA MASA PANDEMI COVID-19 - Ilham, Muhammad; Masdin, Masdin; Hardiyanti, Waode Eti; Desinatalia, Ragil (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to examine the implementation of questioning and reinforcement skills in online learning during the Covid-19 pandemic at SDN 4 Konawe Selatan. This study was qualitative research. The research informants were the principal, 6 teachers, and 2 student representatives. The data in this study were collected through observation, interviews, and documentation. The research data was analyzed through data collection, reduction, presentation, and conclusions. The data were tested for validity using technical and source triangulation. The research results indicated that online learning implemented at SDN 4 Konawe Selatan was asynchronous and synchronous learning models. Most teachers used an asynchronous model in online learning using the whatsapp group. Synchronous learning through the zoom and google meet platforms was only applied in grades V and VI. In the two online learning models, the teachers provided verbal and nonverbal reinforcement, but the implementation of the reinforcement was very limited to asynchronous learning.